2007
DOI: 10.1590/s1516-14392007000100012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ionic strength on the viscosities and water loss of bentonite suspensions containing polymers

Abstract: A study was made of the influence of ionic strength (S) on the apparent (AV) and plastic (PV) viscosities and water loss (WL) of sodium bentonite suspension with polymers. Na-bentonite was dispersed in water (4.86% w/w) of different ionic strengths (S = 0.0, 0.015, 0.030 and 0.045 M) followed by the addition of polymer. Three polymer samples were studied, i.e., low viscosity carboxymethyl cellulose (CMC BV), polyanionic cellulose (PAC), and partially hydrolyzed polyacrylamide (HPAM). The results indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…940,000 g/mol, polysaccharide chains could cause coating of clay particles resulting in a limited dispergation of MMT platelets, similar to the polyanionic cellulose/MMT systems. 14 Also the kind of MMT used had a significant effect on rheoviscometric characteristics of CMS/MMT systems. Applying sodium MMT resulted in an almost double viscosity increase at 1 rpm from 14,000 up to ca.…”
Section: Rheoviscometric Characteristics Of Cms Solutions and Cms/mmtmentioning
confidence: 99%
See 1 more Smart Citation
“…940,000 g/mol, polysaccharide chains could cause coating of clay particles resulting in a limited dispergation of MMT platelets, similar to the polyanionic cellulose/MMT systems. 14 Also the kind of MMT used had a significant effect on rheoviscometric characteristics of CMS/MMT systems. Applying sodium MMT resulted in an almost double viscosity increase at 1 rpm from 14,000 up to ca.…”
Section: Rheoviscometric Characteristics Of Cms Solutions and Cms/mmtmentioning
confidence: 99%
“…However, limited sources on other carboxymethylated polysaccharide/MMT systems including relevant derivatives of cellulose or chitosan are accessible. [13][14][15][16][17] Benchabane and Bekkour 13 investigated rheological behavior of aqueous calcium MMT/carboxymethyl cellulose (CMC) suspensions. They found that CMC (DS 0.65-0.85) coated the clay particles and prevented the reorganization of the agglomerates without enlargement of the MMT interlayer spacing caused by CMC.…”
mentioning
confidence: 99%
“…These systems have been shown to have satisfactory rheological property values at intermediate points, where traditional techniques do not indicate adequate results. Some researchers [12][13][14] have used statistical and mathematical techniques to study the effect of clay compositions and additives on the rheological properties of clay-water systems. This methodology has found application in a number of technological areas [13][14][15][16][17].…”
Section: Influence Of Mgo and Cacl 2 On The Rheological Properties Ofmentioning
confidence: 99%
“…The relationships between the calculated and tabulated F-test values for AV 1 , PV 1 , and AV 2 showed that the models were not only significant but also predictive. For PV 2 , it can be stated that the model was significant [14,21].…”
Section: [Tabela IV -Parâmetros Estatísticos Das Análises De Variâncimentioning
confidence: 99%
“…Many investigators have studied the fluid loss of bentonite dispersions considering different additives. [39][40][41][42] The fluid loss of different prepared mixtures has been shown in Figure 5. Accordingly, for bentonite dispersions without any additive, as bentonite concentration increased, the fluid loss decreased which may be related to presence of higher number of dispersed particle and higher viscosity value, which is a suitable characteristic of drilling fluid.…”
Section: Effect Of Guar Gum and Lime Addition On The Fluidmentioning
confidence: 99%